Descriptive Survey of Preservice Mathematics Teachers’ Perceived Knowledge and Use of Teaching and Learning Materials - Abdul-Wasiu, Rufai; Brilliant Essuman, Isaac; Offei Kwakye, Dennis; Alhassan, Issah (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This study explores how pre-service mathematics teachers use teaching and learning materials (TLMs) in lessons. It highlights the importance of utilising TLMs effectively to create an engaging math learning environment. Barriers and benefits of integrating TLMs are also examined due to limited pre-service teacher readiness literature. A survey involving 272 pre-service mathematics teachers used a quantitative approach to assess their knowledge, perceived barriers, and benefits of Teaching and Learning Materials (TLMs). Results showed that teachers have moderate TLM knowledge, with Trundle wheels being the most recognised and Abacus the least. The main barriers included time constraints, lack of computer skills, and limited TLM resources. However, teachers acknowledged the benefits of TLMs in boosting student engagement and comprehension of math concepts. The study reveals that pre-service teachers have a moderate level of knowledge about different Teaching and Learning Materials (TLMs), but there is variability in their familiarity with various materials. Barriers to using TLMs include a lack of resources in schools, time constraints, limited computer skills, and difficulties in teaching specific mathematical concepts. The research emphasises the importance of training programs for teachers to incorporate TLMs into their lessons effectively. Addressing these challenges is crucial for enhancing math education and providing students with interactive learning experiences. The findings offer valuable insights for policymakers and educators seeking to improve teacher preparation in TLM use.